First evaluation of the Behavioral Addiction Indoor Tanning Screener (BAITS) in a nationwide representative sample - Diehl, Katharina; Breitbart, E. W.; Greinert, R.; Hillhouse, J. J.; Stapleton, J. L.; Schneider, S.; Goerig, Tatiana (British Journal of Dermatology, 2018)
Background: Evidence suggests that indoor tanning may have addictive properties. However, many instruments for measuring indoor tanning addiction show poor validity and reliability. Recently, a new instrument, the Behavioral Addiction Indoor Tanning Screener (BAITS), has been developed. Objectives: To test the validity and reliability of the BAITS by using a multimethod approach. Methods: We used data from the first wave of the National Cancer Aid Monitoring on Sunbed Use, which included a cognitive pretest (August 2015) and a Germany-wide representative survey (October to December 2015). In the cognitive pretest 10 users of tanning beds were interviewed and 3000 individuals aged 14–45 years were included in the representative survey. Potential symptoms of indoor tanning addiction were measured using the BAITS, a brief screening survey with seven items (answer categories: yes vs. no). Criterion validity was assessed by comparing the results of BAITS with usage parameters. Additionally, we tested internal consistency and construct validity. Results: A total of 19·7% of current and 1·8% of former indoor tanning users were screened positive for symptoms of a potential indoor tanning addiction. We found significant associations between usage parameters and the BAITS (criterion validity). Internal consistency (reliability) was good (Kuder–Richardson-20, 0·854). The BAITS was shown to be a homogeneous construct (construct validity). Conclusions: Compared with other short instruments measuring symptoms of a potential indoor tanning addiction, the BAITS seems to be a valid and reliable tool. With its short length and the binary items the BAITS is easy to use in large surveys.
CRIS-Team Scopus Importer:2021-12-06